Sustainability Disclosure, Institutional Ownership and Value of Listed Companies in Nigeria - TERYIMA SAMUEL ORSHI; MOHAMMED ALIYU YUSUF (Asian Journal of Accounting Perspectives, 2024)
Research aim: This study seeks to examine the relationship between sustainability disclosure and the value of listed companies in Nigeria, using institutional ownership as a moderator. Design/ Methodology/ Approach: Data was collected from annual reports and accounts of the firms and daily price listings of the Nigerian Exchange Group from 2014 to 2021. The study uses the Feltham and Ohlson (1995) linear information valuation model to estimate industry-based influence on firm value variations. Research finding: The results show that economic and environmental disclosures as well as institutional ownership significantly and positively impact the value of listed firms, while social disclosure has an insignificant effect. Institutional ownership enhances the positive effect of economic disclosure, but does not enhance the effect of environmental disclosure on firm value, and there is no statistical evidence that it affects the impact of social disclosure on firms’ value. Theoretical contribution/Originality: The study uses stakeholder and legitimacy theories to guide decision-making in sustainability disclosure and institutional ownership. It suggests that greater transparency and accountability in sustainability reporting in Nigeria are needed. Practitioner/Policy implication: The study findings support regulators to mandate sustainability disclosure, raise awareness about its benefits and impact on value, and encourage investor participation in corporate sustainability decision-making. This would enhance the value creation and governance process, ultimately leading to better governance and increased firm value. Research limitation: This study focuses only on sustainability disclosure of Nigerian companies in selected sectors of the economy. Future studies can explore the long-term effects of sustainability disclosures on firm value to understand whether social disclosures yield delayed financial benefits, investigate the impact of sustainability disclosures on firm value across different sectors in Nigeria, and explore how governance frameworks influence the quality of sustainability disclosures and their subsequent effect on firm value.